Changes in Race Performance During the Underwater Phases of a 200 m Bi-Fins Race Simulation After Application of Respiratory Muscle Training-A Case Study in the Current World Record Holder - Tomáš Michalica; Jakub Březina; Marek Polach; Dennis-Peter Born; Jiří Mališ; Zbyněk Svozil; Eva Kociánová (MDPI AG, 2024)
Maximal athletic performance can be limited by various factors, including restricted respiratory function. These limitations can be mitigated through targeted respiratory muscle training, as supported by numerous studies. However, the full potential of respiratory training in competitive finswimming has not been fully investigated. This case study aims to evaluate the effects of eight-week respiratory muscle training (RMT) on performance variability during the underwater phases of a 200 m bi-fins race simulation in an elite finswimmer (current world record holder and multiple world championship medalist). Performance variability was assessed based on pre-test, inter-test, and post-test data. Each measurement included pulmonary function and swim performance evaluations. In this study, underwater performance parameters, such as distance, time, velocity, and number of kicks, were assessed using video analysis synchronized with race timing and evaluated using the Dartfish software. The swimmer followed a 28-day training program with an Airofit PRO™ respiratory trainer between tests, with daily sessions targeting both inspiratory and expiratory muscles. The training involved 6-10 min of targeted exercises per day. Significant improvements were observed in Wilcoxon's paired-sample test between the pre-test and post-test results in terms of underwater distance (p = 0.012; d = 1.26), underwater time (p = 0.012; d = 1.26), and number of underwater kicks (p = 0.043; d = 1.01), resulting in a 14.23% longer underwater distance, 14.08% longer underwater time, and 14.94% increase in underwater kicks. Despite the increased distance and time, underwater velocity remained stable, indicating improved underwater performance efficiency. Despite some improvements, it is not possible to conclude that respiratory muscle training (RMT) can contribute to improved finswimming performance during the underwater phases of a 200 m bi-fins race simulation in this particular athlete's case. Further research with a larger sample size is necessary to fully understand the impact of RMT on finswimming performance.